Contemporary mathematics in context : - Coxford, Arthur F. (Glencoe/McGraw-Hill, 1998)
Contemporary Mathematics in Context engages students in investigation-based, multi-day lessons organized around big ideas. Important mathematical concepts are developed in relevant contexts by students in ways that make sense to them. Courses 1, along with Courses 2 and 3, comprise a core curriculum that upgrades the mathematics experience for all your students. Course 4 is designed for all college-bound students. Developed with funding from the National Science Foundation, each course is the product of a four-year research, development, and evaluation process involving thousands of students in schools across the country.